The deubiquitinase Rpn11 functions as an allosteric ubiquitin sensor to promote substrate engagement by the 26S proteasome - Zaw Min Htet; Ken C. Dong; Andreas Martin (Cell Reports)
Summary: The 26S proteasome is the major compartmental protease in eukaryotic cells, responsible for the ATP-dependent turnover of obsolete, damaged, or misfolded proteins that are delivered for degradation through attached ubiquitin modifications. Besides targeting substrates to the proteasome, ubiquitin was recently shown to promote degradation initiation by modulating proteasome conformational switching, yet the underlying mechanisms are unknown. Here, we use biochemical, mutational, and single-molecule fluorescence resonance energy transfer (FRET)-based approaches to show that the proteasomal deubiquitinase Rpn11 functions as an allosteric sensor and facilitates the early steps of degradation. After substrate recruitment to the proteasome, ubiquitin binding to Rpn11 interferes with conformation-specific interactions of the ubiquitin receptor subunit Rpn10, thereby stabilizing the proteasome’s engagement-competent state and expediting substrate insertion into the ATPase motor for mechanical translocation, unfolding, and Rpn11-mediated deubiquitination. These findings explain how modifications with poly-ubiquitin chains or multiple mono-ubiquitins allosterically promote substrate degradation and allow up to 4-fold faster turnover by the proteasome.